Optimizing RNAi-Target by Nicotiana benthamiana-Soybean Mosaic Virus System Drives Broad Resistance to Soybean Mosaic Virus in Soybean - Jiang, Hua; Li, Kai; Gai, Junyi (Frontiers in Plant Science, 2021)
Soybean mosaic virus (SMV) is a prevalent pathogen of soybean (Glycine max). Pyramiding multiple SMV-resistance genes into one individual is tedious and difficult, and even if successful, the obtained multiple resistance might be broken by pathogen mutation, while targeting viral genome via host-induced gene silencing (HIGS) has potential to explore broad-spectrum resistance (BSR) to SMV. We identified five conserved target fragments (CTFs) from S1 to S5 using multiple sequence alignment of 30 SMV genome sequences and assembled the corresponding target-inverted-repeat constructs (TIRs) from S1-TIR to S5-TIR. Since the inefficiency of soybean genetic transformation hinders the function verification of batch TIRs in SMV-resistance, the Nicotiana benthamiana-chimeric-SMV and N. benthamiana-pSMV-GUS pathosystems combined with Agrobacterium-mediated transient expression assays were invented and used to test the efficacy of these TIRs. From that, S1-TIR assembled from 462 bp CTF-S1 with 92% conservation rate performed its best on inhibiting SMV multiplication. Accordingly, S1-TIR was transformed into SMV-susceptible soybean NN1138-2, the resistant-healthy transgenic T1-plants were then picked out via detached-leaf inoculation assay with the stock-plants continued for progeny reproduction (T1 dual-utilization). All the four T3 transgenic progenies showed immunity to all the inoculated 11 SMV strains under individual or mixed inoculation, achieving a strong BSR. Thus, optimizing target for HIGS via transient N. benthamiana-chimeric-SMV and N. benthamiana-pSMV-GUS assays is crucial to drive robust resistance to SMV in soybean and the transgenic S1-TIR-lines will be a potential breeding source for SMV control in field.